Uncovering the specificity and predictability of tryptophan metabolism in lactic acid bacteria with genomics and metabolomics - Pan, Tong; Pei, Zhangming; Fang, Zhifeng; Wang, Hongchao; Zhu, Jinlin; Zhang, Hao; Zhao, Jianxin; Chen, Wei; Lu, Wenwei (Frontiers in Cellular and Infection Microbiology, 2023)
Abstract: Tryptophan is metabolized by microorganisms into various indole derivatives that have been proven to alleviate diseases and promote human health. Lactic acid bacteria (LAB) are a broad microbial concept, some of which have been developed as probiotics. However, the capacity of most LAB to metabolize tryptophan is unknown. In this study, the aim was to reveal the rule of tryptophan metabolism in LAB by multi-omics. The findings showed that LAB was rich in genes for tryptophan catabolism and that multiple genes were shared among LAB species. Although the number of their homologous sequences was different, they could still form the same metabolic enzyme system. The metabolomic analysis revealed that LAB was capable of producing a variety of metabolites, the majority of which were present at similar levels within the species. A few strains showed strain-specificity in the production of indole-3-lactic acid (ILA), indole-3-acetic acid, and 3-indolealdehyde (IAld). In the genotype-phenotype association analysis, the metabolites of LAB were found to be highly consistent with the outcomes of gene prediction, particularly ILA, indole-3-propionic acid, and indole-3-pyruvic acid. The overall prediction accuracy was more than 87% on average, which indicated the predictability of tryptophan metabolites of LAB. Additionally, genes influenced the concentration of metabolites. The levels of ILA and IAld were significantly correlated with the numbers of aromatic amino acid aminotransferase and amidase, respectively. The unique indolelactate dehydrogenase in Ligilactobacillus salivarius was the primary factor contributing to its large production of ILA. In summary, we demonstrated the gene distribution and production level of tryptophan metabolism in LAB and explored the correlation between genes and phenotypes. The predictability and specificity of the tryptophan metabolites in LAB were proven. These results provided a novel genomic method for the discovery of LAB with tryptophan metabolism potential and offered experimental data for probiotics that produce specific tryptophan metabolites.